Tekanan Institusional Relasional terhadap Kinerja Bisnis Perbankan Syariah di Wilayah Eks Karesidenan Malang - Ubaidi, Abdillah; Syafitri, Andriati Aziizah (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2025)
This research aims to explore the relationship between institutional pressure and dynamic marketing capabilities (DMC), as well as the connection between DMC and the performance of Islamic Banking in the former Malang residency. The study sampled seven banks, comprising 34 analysis units, which include 7 Branch Offices and 27 sub-branch offices. Data processing was conducted using the Smart PLS 3.0 program in alignment with the proposed hypotheses. The findings of this research are as follows: First, institutional infrastructure – comprising both formal and informal rules – significantly influences a firm's ability to adapt to market conditions. Second, DMC is an integrative process that combines a firm's knowledge, skills, and resources to meet market-related business needs.   This research contributes by linking institutional pressures to the development of DMC, emphasizing their cognitive and strategic impact on managers. The implications suggest that firms must align marketing strategies with institutional contexts to achieve sustainable performance, guiding future studies on capability-building in varying regulatory and competitive environments.